Effect Of Advanced Gestation On Cellular Activity In Respiratory System In Females: A Study Of Alveolar Ventilation Parameters In Pregnant Women Of North India - NEERAJ,; JOHN PRAMOD,; JOYDEEP SINGH, (International Journal of Pharma and Bio Sciences, 2012)
This study was conducted on 100 pregnant women in third trimester of uncomplicated pregnancy (cases) and 100 non pregnant women (control). Cases were further subdivided as per the gestational age into two groups of ≤ 34 weeks and > 34 weeks gestation. Pulmonary function test (PFT) parameters FVC, FEV1, PEFR and FEF(25-75%), FEV1/FVC. were evaluated with digital Medspiror. The aim of the study was to assess and compare the change in PFT parameters in third trimester of pregnancy vis a vis those in the non pregnant control subjects of the same age. The study revealed a decrease in PFT values in the ≤ 34 weeks group as compared to the control group which was statistically not significant. But a comparison of PFT in > 34 vs control group, showed significant decrease in all PFT,s except FEV1 / FVC ratio. A similar decline was seen while comparing the subgroups of the study group i.e. ≤34 wks Vs > 34wks groups. This study validates the physiological changes in pulmonary functions during third trimester of pregnancy which if accentuated are likely to affect the outcome of the pregnancy.